A tymovirus from Calopogonium mucunoides in Malaysia is not clitoria yellow vein tymovirus: brief report - Gibbs, A.J.; Mackenzie, A.M.; Abdul-Samad, N. (Springer, 1997)
A tymovirus isolated from Malaysian crops of Calopogonium mucunoides has been shown to have virions that are serologically indistinguishable from those of clitoria yellow vein tymovirus. We have sequenced the virion protein (VP) gene of the virus and have found that although it is a member of the cluster that includes CYVV, it is the most distinct member of that cluster (< 62% sequence identity with all the others), and is clearly a separate species, which we propose should be named calopogonium yellow vein virus. Most of the serological specificity of the virions of tymoviruses seems to reside in the C-terminal hexapeptide of the virion protein.